Variable Wing Span Using the Compliant Spar Concept - Saavedra-Flores, E (2013)
This paper develops and models the Compliant Spar concept that allows the wing span to be varied to provide roll control and enhance the operational performance for a medium altitude long endurance (MALE) UAV. The wing semispan is split into morphing partitions and the concept maybe incorporated in each partition; however only the tip partition is considered here. The Compliant Spar is made of compliant joints arrange in series to allow the partition to be flexible under axial (spanwise) loads but at the same time stiff enough to resist bending loads. Each compliant joint consists of two concentric overlapping Aluminium (AL) 2024-T3 tubes joined together using elastomeric material. Under axial (spanwise) loading, the elastomeric material deforms in shear allowing the overlapping distance between the tubes to vary and hence the length (in the spanwise direction) of the joint/spar to vary. High fidelity modelling of the concept is performed. Then, multidisciplinary design optimisation (MDO) studies are performed to minimise the axial stiffness and the structural mass of the concept for various design constraints. The flexible skin and actuation system to be used are also addressed. © 2013 by Rafic Mohammad Ajaj.